Periosteal reaction-like lesions at the cranial aspect of the humeral diaphysis have a high prevalence in older, large breed dogs and may represent entheses of the superficial pectoral muscles - Nickel, Mareike-Kristin; Schikowski, Lisa; Staszyk, Carsten; Schaub, Sebastian; Justus Liebig University Giessen (My University, 2023)
Authors have commonly observed lamellar periosteal new bone formation at the cranial aspect of the humeral diaphysis in mediolateral radiographs of the humerus for large breed dogs with no evidence of pain or lameness. The aim of this retrospective, analytical study was to investigate the appearance and prevalence of “humeral periosteal reaction-like lesions” (HPRLL) in dogs and identify any predispositions. Mediolateral radiographs of humeri were evaluated and the presence and extent of “humeral periosteal reaction-like lesions” at the cranial aspect of the humerus were recorded. Macroscopic and histological examination of the humeri were performed for one dog with HPRLL. A total of 2877 mediolateral radiographs of 1727 dogs were included and focal or extended periosteal reaction-like lesions were found in 643 humeri of 387 dogs. Body weight ≥ 30 kg and age ≥ 7 years had a statistically significant, positive effect (P < 0.001) on the presence of HPRLL. German Shepherd dogs and Rottweilers were overrepresented in the group with HPRLL (P < 0.01). At the level of the HPRLL, the enthesis of the superficial pectoral muscles (M. pectoralis descendens and M. pectoralis transversus) to the Crista tuberculi majoris and Crista humeri were macroscopically and histologically identified. The authors propose that higher mechanical loads to the enthesis in large breed dogs may lead to physiological, age-related remodeling processes of the muscular attachment. The finding should not be confused with a pathological condition such as bone neoplasia.
Keywords: ddc:630